Bionic metal nano-enzyme photocatalyst as well as preparation method and application thereof
By constructing a bionic metal nanoenzyme photocatalyst with asymmetric ligands, the problems of low photocatalytic conversion efficiency of polyester plastics and poor stability of natural enzymes in the prior art are solved, and PET plastic conversion at high efficiency and low temperatures are achieved, with excellent catalytic activity and structural stability.
Patent Information
- Application Number
- CN202411978948.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-11
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The prior art is difficult to efficiently convert waste polyester plastics into high value-added chemicals through photocatalysts, and natural enzyme catalysts have poor stability when temperature and pH value change.
Using a bionic metal nanoenzyme photocatalyst, the D-MIL-101 (Fe) and A-MIL-101 (Fe) catalysts were constructed through Fe-MOF as a template, and the active site and structural stability of the catalyst were improved by using asymmetric ligands.
It realizes high-efficiency photocatalytic conversion of polyester plastics, improves solar energy utilization and electron hole separation capabilities, significantly improves catalytic activity and structural stability, and can efficiently convert PET plastics at low temperatures.
Smart Images

Figure CN119798693A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of catalysts, and in particular relates to a bionic metal nanoenzyme photocatalyst and a preparation method and application thereof. Background Art
[0002] Plastics are widely used in various industries as man-made materials with excellent properties such as low cost, durability and processability. In particular, polyester plastics can be reprocessed into fibers, beverage bottles, electronic devices, etc., making positive contributions to human development. However, despite the good physical and chemical properties and practicality of plastics, the amount of plastics recycled after consumption still cannot meet the needs of sustainable development. Traditional incineration and landfill strategies usually lead to serious resource waste and environmental pollution. At present, the mechanical recycling of waste plastics is regarded as a downcycling process because the structural properties of plastics will degrade after continuous grinding and melting cycles. In contrast, chemical upcycling, as a "closed-loop recycling" method, can convert waste plastics into high-value-added raw materials. In recent years, chemical recycling has mainly been based on processes such as thermal catalysis / pyrolysis to recycle waste plastics, but its depolymerization usually requires a large amount of energy input to achieve CC, CO, and CH bond cleavage, which undermines the economic feasibility of these processes. Therefore, the development of cost-effective and energy-efficient chemical recycling processes plays an important role in achieving a more sustainable future.
[0003] Among the existing technologies, photocatalytic upgrading of post-consumer plastics is a more attractive solution, which can convert solar energy into chemical energy and recycle plastics into high-value-added chemicals. So far, people have designed catalysts through strategies such as constructing heterojunctions, regulating defects, and morphology and size, which can effectively convert plastic waste into fine chemicals, but the high energy barrier of cracking the carbon bonds of the plastic backbone inhibits the overall photocatalytic efficiency. In addition, the random breakage of polymer chains will lead to poor product selectivity. Therefore, it is necessary to design and construct advanced photocatalysts to achieve the thermodynamic and kinetic optimal reaction path of waste plastics.
[0004] At present, enzymatic depolymerization of polyester plastics provides a low-energy and sustainable way for plastic recycling, and hydrolases, peroxidases and oxidases have been shown to degrade polymers in the surrounding environment. Among the hydrolases reported so far, lipases, cutinases, etc. can degrade polyethylene terephthalate (PET). In addition, protein engineering strategies have been used to improve the catalytic activity and thermal stability of these PET degrading enzymes. However, it is worth noting that these natural hydrolases are usually inactivated due to temperature changes, pH fluctuations, and poor stability when pollutants and additives are present in waste plastics. Therefore, how to improve the activity and stability of enzymes has become a challenge. Biomimetic enzyme catalysis can combine high enzyme activity with the stability of inorganic materials, and it shows great potential in biomass conversion. Among them, nanozymes have the advantages of high structural stability and adjustable catalytic active sites. They can effectively cope with the harsh reaction conditions in the process of enzyme-catalyzed plastic depolymerization, reduce energy consumption in plastic recycling, and promote the efficient recovery of waste plastics into plastic monomers and fine chemicals, which is conducive to the realization of "closed-loop" recycling of plastics, and is of great significance to the development of a low-carbon circular economy.
[0005] Therefore, how to construct a bionic enzyme catalyst that can promote the recycling of waste plastics and use it to efficiently produce high-value-added chemicals from polyester plastics is a technical problem that technical personnel in this field urgently need to solve. Summary of the invention
[0006] In order to solve the above technical problems, the present invention proposes a bionic metal nanoenzyme photocatalyst and a preparation method and application thereof.
[0007] To achieve the above object, the present invention provides the following technical solutions:
[0008] A bionic metal nanozyme photocatalyst, wherein the bionic metal nanozyme photocatalyst is a metal organic framework material; the ligand of the metal organic framework material comprises a symmetrical ligand and / or an asymmetrical ligand;
[0009] The symmetrical ligand is 2-aminoterephthalic acid;
[0010] The asymmetric ligand is benzoic acid.
[0011] Beneficial effects: The present invention uses MOF as a template and constructs an asymmetric ligand D-MIL-101 (Fe) bionic metal nanozyme photocatalyst and a symmetric ligand A-MIL-101 (Fe) bionic metal nanozyme photocatalyst with excellent photocatalytic conversion performance of plastic PET through a simple hydrothermal synthesis method. The metal nanozyme photocatalyst maintains the original skeleton structure characteristics of Fe-MOF, presents an octahedral structure, and has a rich specific surface area and defect structure, which is conducive to the diffusion of reaction substrates and products. Among them, the asymmetric ligand D-MIL-101 (Fe) bionic metal nanozyme photocatalyst has better performance, the asymmetric active site is conducive to contact with the substrate to promote the breaking of the plastic ester bond, and the full exposure of the active site can effectively improve the utilization rate of sunlight and accelerate the separation of photogenerated holes and electrons, so it has a more excellent photocatalytic activity.
[0012] A method for preparing a bionic metal nanoenzyme photocatalyst comprises the following steps:
[0013] The biomimetic metal nanoenzyme photocatalyst is obtained by dissolving ferric chloride and a ligand in a solvent to obtain a mixed solution, and then subjecting the mixed solution to a hydrothermal reaction.
[0014] The ligands include symmetrical ligands and / or asymmetrical ligands;
[0015] The symmetrical ligand is 2-aminoterephthalic acid;
[0016] The asymmetric ligand is benzoic acid.
[0017] Preferably, the molar ratio of the ferric chloride to the ligand is 2:1-6:1.
[0018] More preferably, the molar ratio of ferric chloride to ligand is (2-3):1.
[0019] Beneficial effect: Under the above ratio, the obtained catalyst has an octahedral structure and uniform particle size, and has the best catalytic activity.
[0020] Preferably, the temperature of the hydrothermal reaction is 100-150° C. and the time is 8-14 h.
[0021] More preferably, the temperature of the hydrothermal reaction is 110° C. and the time is 10 h.
[0022] Beneficial effect: Under the above conditions, the obtained catalyst maintains a good structure. If the temperature or time is higher than the above conditions, the material preparation will fail.
[0023] Preferably, when the ligand comprises a symmetric ligand and an asymmetric ligand, the molar ratio of the symmetric ligand to the asymmetric ligand is 1:1-1:0.1.
[0024] More preferably, the molar ratio of 2-aminoterephthalic acid to benzoic acid is 0.3:0.7.
[0025] Beneficial effects: Under the above ratio, the obtained catalyst structure presents a defective structure and has the best catalytic activity. If it is lower than the above ratio, the amount of asymmetric ligand added increases, which will lead to unstable structure of the catalyst and reduced catalytic activity. If it is higher than the above ratio, the amount of asymmetric ligand added decreases, which will lead to fewer catalyst defects and reduced catalytic activity.
[0026] Preferably, the concentration of ferric chloride in the mixed solution is 100-300 mmol L -1 The concentration of the ligand was 20-62 mmol L -1 , more preferably 41-42 mmol L -1 .
[0027] Beneficial effect: A good ligand ratio can be maintained at the above concentration. If the concentration is higher / lower than the above concentration, it will lead to reduced material synthesis and unsuccessful material preparation.
[0028] Preferably, the solvent is DMF.
[0029] Beneficial effects: Using DMF as solvent can make the raw materials react fully, and the obtained catalyst has the best activity.
[0030] Application of a biomimetic metal nanozyme photocatalyst in the photocatalytic conversion of plastics.
[0031] Preferably, the plastic is polyethylene terephthalate.
[0032] Beneficial effects: PET is polyethylene terephthalate, and the catalyst in the present invention can break the ester bonds in the PET molecules under photocatalytic conditions to form monomer terephthalic acid.
[0033] Preferably, the temperature of the photocatalytic conversion is 60-95° C. and the time is 2-10 h.
[0034] More preferably, the temperature of the photocatalytic conversion is 75° C. and the time is 10 h.
[0035] Beneficial effects: The catalytic effect is best under the above temperature conditions. If the temperature is higher / lower than the above temperature, the activity of the pseudo-enzyme catalyst will be lower and the catalytic degradation of PET will be incomplete.
[0036] Compared with the prior art, the present invention has the following advantages and technical effects:
[0037] The present invention constructs an A-MIL-101 (Fe) bionic metal nanozyme photocatalyst with a symmetrical ligand and a D / A-MIL-101 (Fe) bionic metal nanozyme photocatalyst with an asymmetrical ligand based on Fe-MOF as a template, and uses the catalyst to efficiently catalyze the conversion of polyethylene terephthalate (PET) plastic to produce terephthalic acid, and can also achieve efficient conversion of PET plastic products in life at low temperatures.
[0038] Secondly, the D-MIL-101 (Fe) bionic metal nanozyme photocatalyst constructed by the present invention has a further improved ability to absorb solar energy compared to the A-MIL-101 (Fe) bionic metal nanozyme photocatalyst, a significantly enhanced electron-hole separation ability, and a significantly accelerated free radical generation rate. In addition, the bionic enzyme photocatalyst prepared by the present invention can achieve selective catalytic conversion of plastic PET. Compared with natural enzyme-catalyzed chemical recycling technology, it has the advantages of high structural stability and high efficiency, is easy to mass produce, and can be used for efficient and highly selective chemical recycling of plastics, showing broad commercial application value. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] The drawings constituting a part of the present application are used to provide a further understanding of the present application. The illustrative embodiments and descriptions of the present application are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:
[0040] Figure 1 is the X-ray powder diffraction pattern of A-MIL-101(Fe) in Example 1 of the present invention;
[0041] Figure 2 D in Example 2 of the present invention 0.7 - X-ray powder diffraction pattern of MIL-101(Fe);
[0042] Figure 3 is a scanning electron microscope image of A-MIL-101(Fe) in Example 1 of the present invention;
[0043] Figure 4 D in Example 2 of the present invention 0.7 - Scanning electron micrograph of MIL-101(Fe);
[0044] Figure 5 This is the particle size distribution image of A-MIL-101 (Fe) in Example 1 of the present invention;
[0045] Figure 6 D in Example 2 of the present invention 0.7 - Particle size distribution image of MIL-101(Fe);
[0046] Figure 7 It is the solid ultraviolet diffuse reflectance image of A-MIL-101 (Fe) in Example 1 of the present invention;
[0047] Figure 8 D in Example 2 of the present invention 0.7 - Solid UV diffuse reflectance image of MIL-101(Fe);
[0048] Fig. 9 This is the nuclear magnetic resonance spectrum of terephthalic acid, a photocatalytic product of A-MIL-101 (Fe) in Example 1 of the present invention;
[0049] Fig.10 D in Example 2 of the present invention 0.7 -NMR spectrum of terephthalic acid, a photocatalytic product of MIL-101(Fe);
[0050] Fig.11 This is a performance diagram of the photocatalytic PET conversion of the A-MIL-101 (Fe) catalyst in Example 1 of the present invention;
[0051] Fig.12 D in Example 2 of the present invention 0.7 -Photocatalytic PET conversion performance diagram of MIL-101(Fe) catalyst;
[0052] Fig.13 For the present invention D 0.7 -MIL-101(Fe) and A-MIL-101(Fe) catalysts photocatalytic conversion of PET to terephthalic acid yield performance diagram;
[0053] Fig.14 D in Example 2 of the present invention 0.7 -Performance diagram of the photocatalytic conversion of PET plastic bags, PET straws, and PET packaging boxes in daily life using MIL-101(Fe) catalyst. DETAILED DESCRIPTION
[0054] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0055] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.
[0056] In an embodiment of the present invention, a biomimetic metal nanozyme photocatalyst is provided, comprising a symmetrical ligand and / or an asymmetrical ligand;
[0057] The symmetrical ligand is 2-aminoterephthalic acid;
[0058] The asymmetric ligand is benzoic acid.
[0059] The present invention also provides a method for preparing a bionic metal nanozyme photocatalyst, comprising the following steps:
[0060] The biomimetic metal nanoenzyme photocatalyst is obtained by dissolving ferric chloride and a ligand in a solvent to obtain a mixed solution, and then subjecting the mixed solution to a hydrothermal reaction.
[0061] The ligands include symmetrical ligands and / or asymmetrical ligands;
[0062] The symmetrical ligand is 2-aminoterephthalic acid;
[0063] The asymmetric ligand is benzoic acid.
[0064] In a preferred embodiment, the molar ratio of the ferric chloride to the ligand is 2:1-6:1.
[0065] In a more preferred embodiment, the molar ratio of ferric chloride to ligand is (2-3):1.
[0066] In a preferred embodiment, the temperature of the hydrothermal reaction is 100-150°C, and the time is 8-14 hours. Within this range, the higher the temperature of the hydrothermal reaction, the shorter the time required for the reaction to be complete; for example, when the temperature of the hydrothermal reaction is 150°C, the reaction time should be controlled within 8 hours; when the temperature of the hydrothermal reaction is 100°C, the reaction time should be controlled within 14 hours.
[0067] Taking the reaction rate and energy consumption into consideration, in some typical but non-limiting embodiments, the temperature of the hydrothermal reaction is 110° C. and the time is 10 h.
[0068] In a preferred embodiment, when the ligand comprises a symmetric ligand and an asymmetric ligand, the molar ratio of the symmetric ligand to the asymmetric ligand is 1:1-1:0.1.
[0069] In a more preferred embodiment, the molar ratio of 2-aminoterephthalic acid to benzoic acid is 0.3:0.7.
[0070] In a preferred embodiment, the concentration of ferric chloride in the mixed solution is 100-300 mmol L -1 The concentration of the ligand was 20-62 mmol L -1 , more preferably 41-42 mmol L -1 .
[0071] In a preferred embodiment, the solvent is DMF.
[0072] The embodiment of the present invention also provides an application of a bionic metal nanozyme photocatalyst in the photocatalytic conversion of plastics.
[0073] In a preferred embodiment, the plastic is polyethylene terephthalate.
[0074] In a preferred embodiment, the temperature of the photocatalytic conversion is 60-95° C. and the time is 2-10 h.
[0075] In a more preferred embodiment, the temperature of the photocatalytic conversion is 75° C. and the time is 10 hours.
[0076] Unless otherwise specified, the raw materials in the examples of the present invention were purchased from commercial sources;
[0077] Among them, the molecular weight of PET is 100,000.
[0078] Unless otherwise specified, the room temperature or normal temperature in the embodiments of the present invention refers to 25±3°C.
[0079] Example 1
[0080] A method for preparing a bionic metal nanoenzyme photocatalyst comprises the following steps:
[0081] 1080 mg (6.66 mmol) of ferric chloride and 450 mg (2.48 mmol) of 2-aminoterephthalic acid were weighed and dissolved in 30 mL of DMF. After dissolution by ultrasonic oscillation, the two solutions were mixed to obtain a mixed solution with a ligand concentration of 41.4 mmol L -1 ; The mixed solution was transferred to a reactor and the A-MIL-101(Fe) catalyst was synthesized by a hydrothermal reaction, wherein the hydrothermal reaction conditions were a constant temperature reaction at 110°C for 10 hours. After the reaction, the obtained precipitate (A-MIL-101(Fe) precursor) was washed with anhydrous ethanol and dried at 70°C for 12 hours to obtain the A-MIL-101(Fe) catalyst.
[0082] Example 2
[0083] A method for preparing a bionic metal nanoenzyme photocatalyst comprises the following steps:
[0084] 1080 mg of ferric chloride was weighed and dissolved in 30 mL of DMF to obtain a ferric chloride solution; 135 mg (0.75 mmol) of 2-aminoterephthalic acid and 212.35 mg (1.75 mmol) of benzoic acid (the molar ratio of 2-aminoterephthalic acid to benzoic acid was 0.3:0.7) were dissolved in 30 mL of DMF to obtain a ligand solution; the two solutions were mixed after dissolution by ultrasonic oscillation to obtain a mixed solution with a ligand concentration of 41.6 mmol L -1 ; The mixed solution was transferred to a reactor and D was prepared by hydrothermal synthesis 0.7 -MIL-101(Fe), wherein the hydrothermal reaction conditions are constant temperature reaction at 110°C for 10 hours, after the reaction is completed, the obtained precipitate (D 0.7 -MIL-101(Fe)) was washed with anhydrous ethanol and dried at 70 °C for 12 h to obtain D 0.7 -MIL-101(Fe) catalyst.
[0085] Example 3
[0086] A method for preparing a bionic metal nanoenzyme photocatalyst comprises the following steps:
[0087] Weigh 1080 mg of ferric chloride, 360 mg of 2-aminoterephthalic acid, and 60.67 mg of benzoic acid (the molar ratio of 2-aminoterephthalic acid to benzoic acid is 0.8:0.2) and dissolve them in 30 mL of DMF. After dissolving by ultrasonic oscillation, the two solutions are mixed to obtain a mixed solution with a ligand concentration of 41.5 mmol / L -1 ; The mixed solution was transferred to a reactor and D was prepared by hydrothermal synthesis 0.7 -MIL-101(Fe), wherein the hydrothermal reaction conditions are constant temperature reaction at 110°C for 10 hours, after the reaction is completed, the obtained precipitate (D 0.7 -MIL-101(Fe)) was washed with anhydrous ethanol and dried at 70 °C for 12 h to obtain D 0.8 -MIL-101(Fe) catalyst.
[0088] Example 4
[0089] A method for preparing a bionic metal nanoenzyme photocatalyst comprises the following steps:
[0090] Weigh 1080 mg of ferric chloride, 225 mg of 2-aminoterephthalic acid, and 91 mg of benzoic acid (the molar ratio of 2-aminoterephthalic acid to benzoic acid is 0.5:0.5) and dissolve them in 30 mL of DMF. After dissolving by ultrasonic oscillation, the two solutions are mixed to obtain a mixed solution with a ligand concentration of 33.1 mmol / L -1 ; The mixed solution was transferred to a reactor and D was prepared by hydrothermal synthesis0.7 -MIL-101(Fe), wherein the hydrothermal reaction conditions are constant temperature reaction at 110°C for 10 hours, after the reaction is completed, the obtained precipitate (D 0.7 -MIL-101(Fe)) was washed with anhydrous ethanol and dried at 70 °C for 12 h to obtain D 0.5 -MIL-101(Fe) catalyst.
[0091] Technical effects:
[0092] A-MIL-101(Fe) (20 mg) prepared in Example 1 and Example 2, D 0.7 -MIL-101(Fe)(20 mg) was added to 100 mL of 50 mg mL -1 In the PET suspension, the temperature was adjusted between 60-95°C, and a 300W xenon lamp was used as the light source for the photocatalytic experiment. Then, illumination was performed, and samples were taken at regular intervals, and the results were analyzed using nuclear magnetic resonance spectroscopy.
[0093] A Hitachi SU-3500 electron microscope was used to observe the A-MIL-101 (Fe) precursor and D prepared in Example 1 and Example 2. 0.7 -MIL-101(Fe) was used for structural characterization.
[0094] Figure 1 and Figure 2 They are respectively A-MIL-101(Fe) in Example 1 of the present invention and D in Example 2 0.7 -X-ray powder diffraction pattern (XRPD pattern) of MIL-101(Fe); As can be seen from the figure, D 0.7 -MIL-101(Fe) has a similar structure to A-MIL-101(Fe), and the diffraction peak decreases.
[0095] Figure 3 and Figure 4 They are respectively A-MIL-101(Fe) in Example 1 of the present invention and D in Example 2 0.7 -Scanning electron microscope image of MIL-101(Fe); As can be seen from the figure, D 0.7 -MIL-101(Fe) morphology is octahedral and the size is reduced.
[0096] Figure 5 , Figure 6 They are respectively A-MIL-101(Fe) in Example 1 of the present invention and D in Example 2 0.7 -Particle size distribution image of MIL-101(Fe); It can be seen from the figure that the particle size of the bionic metal nanozyme catalysts prepared with two different ligands is smaller than that of the bionic metal nanozyme catalyst prepared with the same ligand.
[0097] Figure 7 , Figure 8 They are respectively A-MIL-101(Fe) in Example 1 of the present invention and D in Example 2 0.7 - Solid UV diffuse reflectance image of MIL-101(Fe); As can be seen from the figure, D 0.7 -MIL-101(Fe) has a wider light absorption range than A-MIL-101(Fe).
[0098] Fig. 9 , Fig.10 They are respectively A-MIL-101(Fe) in Example 1 of the present invention and D in Example 2 0.7 -NMR spectrum of terephthalic acid, the photocatalytic product of MIL-101(Fe); the figure shows the presence of terephthalic acid as the product.
[0099] Fig.11 This is a performance diagram of the photocatalytic PET conversion of the A-MIL-101 (Fe) catalyst in Example 1 of the present invention;
[0100] Fig.12 D in Example 2 of the present invention 0.7 -Photocatalytic PET conversion performance diagram of MIL-101(Fe) catalyst;
[0101] Fig.13 A-MIL-101 (Fe) in Example 1 and D in Example 2 of the present invention 0.7 -Performance diagram of terephthalic acid yield of MIL-101(Fe) catalyst photocatalytic PET conversion;
[0102] Fig.14 D in Example 2 of the present invention 0.7 -Performance diagram of the photocatalytic conversion of PET plastic bags, PET straws, and PET packaging boxes in daily life using MIL-101(Fe) catalyst.
[0103] Depend on Fig.11 , 12 It can be seen that the bionic nanozyme catalyst of Example 2 can convert PET plastic into terephthalic acid within 10 hours, and the plastic conversion rate reaches more than 82%; the bionic nanozyme catalyst of Example 1 can convert PET plastic into terephthalic acid within 10 hours, and the plastic conversion rate is less than 50%; Fig.13 It can be seen that the bionic nanozyme catalyst prepared in Example 2 can convert PET plastic into terephthalic acid within 10 hours, and the terephthalic acid yield reaches more than 93%; Fig.14 It can be seen that D 0.7-MIL-101(Fe) bionic nanocatalyst can still achieve a conversion efficiency of more than 80% when applied to PET plastic bags, PET packaging boxes, PET straws and other products in daily life within 10 hours, reflecting good practicality.
[0104] In summary, the bionic metal nanozyme D / A-MIL-101 (Fe) catalyst provided by the present invention presents an octahedral structure, and the introduction of asymmetric ligands reduces the particle size of the D-MIL-101 (Fe) catalyst, and the rich specific surface area and asymmetric active sites are conducive to promoting the diffusion of reaction products and substrates during the catalytic process; a large number of exposed active sites can improve the absorption efficiency of light, and the presence of defective structures and the energy band matching effect effectively promote the separation of photogenerated electrons-holes, and promote the migration of electrons to the catalyst site for efficient conversion of PET plastics into high value-added chemicals terephthalic acid, and at the same time, the bionic nanocatalyst can be used to convert plastic products in life, showing good applicability. In addition, compared to natural enzyme-catalyzed chemical recycling technology, the present invention utilizes the asymmetric active site of the bionic nanozyme D-MIL-101 (Fe) catalyst to simulate the contact between the enzyme catalytic site and the substrate, which is used for efficient photocatalytic recycling of plastic technology, with the advantages of high catalyst structure stability, high plastic catalytic conversion efficiency, green environmental protection, easy to batch production, showing a wide range of commercial application value.
[0105] The above are only preferred specific implementations of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.
Claims
1. A bionic metal nanozyme photocatalyst, characterized in that: The bionic metal nanozyme photocatalyst is a metal organic framework material; the ligand of the metal organic framework material includes a symmetrical ligand and / or an asymmetrical ligand; The symmetrical ligand is 2-aminoterephthalic acid; The asymmetric ligand is benzoic acid.
2. A method for preparing the biomimetic metal nanozyme photocatalyst according to claim 1, characterized in that: The following steps are involved: The biomimetic metal nanoenzyme photocatalyst is obtained by dissolving ferric chloride and a ligand in a solvent to obtain a mixed solution, and then subjecting the mixed solution to a hydrothermal reaction. The ligands include symmetrical ligands and / or asymmetrical ligands; The symmetrical ligand is 2-aminoterephthalic acid; The asymmetric ligand is benzoic acid.
3. The method for preparing a biomimetic metal nanozyme photocatalyst according to claim 2, characterized in that: The temperature of the hydrothermal reaction is 100-150° C. and the time is 8-14 hours.
4. The method for preparing a biomimetic metal nanozyme photocatalyst according to claim 2, characterized in that: The molar ratio of the ferric chloride to the ligand is (2-6):
1.
5. The method for preparing a biomimetic metal nanozyme photocatalyst according to claim 2, characterized in that: When the ligand includes a symmetrical ligand and an asymmetrical ligand, the molar ratio of the symmetrical ligand to the asymmetrical ligand is 1:(0.1-1).
6. The method for preparing a biomimetic metal nanozyme photocatalyst according to claim 2, characterized in that: In the mixed solution, the concentration of ferric chloride is 100-300 mmol L -1 The concentration of the ligand was 20-62 mmol L -1 .
7. The method for preparing a biomimetic metal nanozyme photocatalyst according to claim 2, characterized in that: The solvent is DMF.
8. Use of a bionic metal nanozyme photocatalyst as claimed in claim 1 in the photocatalytic conversion of plastics.
9. The use according to claim 8, characterized in that: The plastic is polyethylene terephthalate.
10. The use according to claim 8, characterized in that: The temperature of the photocatalytic conversion is 60-95° C. and the time is 2-10 hours.
Citation Information
Patent Citations
Photocatalyst and preparation method and application thereof
CN110327976A
Bimetallic MOFs catalyst and preparation method and application thereof
CN110787840A
Preparation method and application of amino-modified Fe / Cu-MOF photocatalyst
CN113318791A
Bionic nano-enzyme as well as preparation method and application thereof
CN114768872A
Method for improving catalytic selectivity of nano-enzyme to specific substrate
CN118080012A